Species-specific and seasonal differences in the resistance of salt-marsh vegetation to wave impact - Reents, Svenja; Möller, Iris; Evans, Ben R.; Schoutens, Ken; Jensen, Kai; Paul, Maike; Bouma, Tjeerd J.; Temmerman, Stijn; Lustig, Jennifer; Kudella, Matthias; Nolte, Stefanie (Frontiers in Marine Science, 2022)
The coastal protection function provided by the vegetation of tidal wetlands (e.g. salt marshes) will play an important role in defending coastlines against storm surges in the future and depend on how these systems respond to such forcing. Extreme wave events may induce vegetation failure and thereby risking loss of functionality in coastal protection. However, crucial knowledge on how hydrodynamic forces affect salt-marsh vegetation and whether plant properties might influence plant resistance is missing. In a true-to-scale flume experiment, we exposed two salt-marsh species to extreme hydrodynamic conditions and quantified wave-induced changes in plant frontal area, which was used to estimate plant damage. Additionally, some plants were artificially weakened (via drought) as we expected seasonal changes in plant resistance, as the leaves and stems of examined species die off during the winter and their biophysical properties may undergo considerable modifications. Morphological, biomechanical as well as biochemical plant properties were assessed to better explain potential differences in wave-induced plant damage. Our results indicate that the plants were more robust than expected, with pioneer species Spartina anglica showing a higher resistance than the high-marsh species Elymus athericus. Furthermore, wave-induced plant damage mostly occurred in the upper part of the vegetation canopy and thus higher canopies (i.e. Elymus athericus) were more vulnerable to damage. Besides a taller canopy, Elymus athericus had weaker stems than Spartina anglica, suggesting that biomechanical properties (flexural stiffness) also played a role in defining plant resistance. Under the highest wave conditions, we also found seasonal differences in the vulnerability to plant damage but only for Elymus athericus. Although we found higher concentrations of a strengthening compound (biogenic silica) in the plant material of the weakened plants, the flexibility of the plant material was not affected indicating that the drought might not has been applied long enough. Nevertheless, this study yields important implications since we demonstrate a high robustness of the salt-marsh vegetation as well as species-specific and seasonal differences in the vulnerability to plant damage.